2021
DOI: 10.3389/fmolb.2021.764222
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Mediated Crosstalk Between Tumor and Tumor-Associated Macrophages

Abstract: Exosomes are nanosized vesicles, derived from the endolysosomal compartment of cells and can shuttle diverse biomolecules such as nucleic acids, proteins, lipids, amino acids, and metabolites, which can reflect their origin cells. Delivery of these cargoes to recipient cells enables exosomes to influence diverse cellular functions. As one of the most abundant immune cells in the tumor microenvironment, tumor-associated macrophages (TAMs) are educated by the tumor milieu, which is rich in cancer cells and strom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 144 publications
(200 reference statements)
0
29
0
Order By: Relevance
“…The following studies also confirmed that all eukaryotes and prokaryotes could produce EVs, and it was considered that cells used these EVs as cargo transporters to transfer unwanted materials outwards [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. However, recent research has shown that EVs are crucial for intercellular communication throughout normal and pathological development [ 11 , 12 , 13 , 14 , 15 ]; in fact, some of them are involved in cancer progression [ 16 , 17 , 18 , 19 ], obesity and metabolic diseases [ 20 , 21 , 22 , 23 , 24 ], inflammatory and autoimmune pathogenesis [ 25 , 26 , 27 ]. Nowadays, various studies revealed that EVs are used in several clinical applications such as disease diagnosis and development of vaccines, drug distribution, and extracellular vesicle (EV)-based therapies [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following studies also confirmed that all eukaryotes and prokaryotes could produce EVs, and it was considered that cells used these EVs as cargo transporters to transfer unwanted materials outwards [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. However, recent research has shown that EVs are crucial for intercellular communication throughout normal and pathological development [ 11 , 12 , 13 , 14 , 15 ]; in fact, some of them are involved in cancer progression [ 16 , 17 , 18 , 19 ], obesity and metabolic diseases [ 20 , 21 , 22 , 23 , 24 ], inflammatory and autoimmune pathogenesis [ 25 , 26 , 27 ]. Nowadays, various studies revealed that EVs are used in several clinical applications such as disease diagnosis and development of vaccines, drug distribution, and extracellular vesicle (EV)-based therapies [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research has shown that EVs are crucial for intercellular communication throughout normal and pathological development [ 11 , 12 , 13 , 14 , 15 ]; in fact, some of them are involved in cancer progression [ 16 , 17 , 18 , 19 ], obesity and metabolic diseases [ 20 , 21 , 22 , 23 , 24 ], inflammatory and autoimmune pathogenesis [ 25 , 26 , 27 ]. Nowadays, various studies revealed that EVs are used in several clinical applications such as disease diagnosis and development of vaccines, drug distribution, and extracellular vesicle (EV)-based therapies [ 17 , 18 , 19 ]. Electron microscopic imaging and nanoparticle tracking analysis (NTA) are the primary tools for the characterization of the morphology and size of vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…M1 macrophages display important antitumor activities and are involved in the immune system’s response to cancer, whereas M2 macrophages (also known as tumor-associated macrophages or M2-TAMs) promote cancer progression and contribute to multidrug resistance in cancer therapy [ 5 , 6 ]. Therefore, multiple antitumoral approaches are being explored to induce the shift of M2-TAMs to proinflammatory M1 macrophages [ 7 , 8 , 9 ]. Among the new immunotherapeutic treatments, approaches based on extracellular vesicles (EVs) are receiving attention for their antitumor potential and the bioengineering possibilities that they can offer [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…EVs derived from M1 macrophages have demonstrated important antitumor properties against different types of cancer, including melanoma and breast cancer [ 18 ]. M1-derived EVs (M1-EVs) repolarize M2 macrophages and activate the resident M1 macrophages, thereby creating a proinflammatory TME that decreases tumor growth and induces apoptosis in cancer cells [ 7 , 8 ]. M1-EVs are also efficient adjuvants and nanocarriers that enhance the anticancer properties of cytostatic drugs and monoclonal antibodies in vitro and in vivo [ 8 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation